2014
DOI: 10.1002/jat.2984
|View full text |Cite
|
Sign up to set email alerts
|

Mode of action human relevance (species concordance) framework: Evolution of the Bradford Hill considerations and comparative analysis of weight of evidence

Abstract: The mode of action human relevance (MOA/HR) framework increases transparency in systematically considering data on MOA for end (adverse) effects and their relevance to humans. This framework continues to evolve as experience increases in its application. Though the MOA/HR framework is not designed to address the question of “how much information is enough” to support a hypothesized MOA in animals or its relevance to humans, its organizing construct has potential value in considering relative weight of evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(109 citation statements)
references
References 16 publications
(31 reference statements)
1
108
0
Order By: Relevance
“…Considerations related to weight of evidence for MOA have been additionally articulated in a subsequent publication (Meek et al 2014b) and evolved in international collaborative efforts on adverse outcome pathways (AOPs) (OECD Handbook 2016;Becker et al 2015;Edwards et al 2016). The US EPA (2014) guidance on Data-Derived Extrapolation Factors also contributes significantly to CSAF evolution by encouraging the identification and use of TK or TD data to inform the magnitude of interspecies differences and human variability (e.g.…”
Section: Updating and Revision Of The Guidancementioning
confidence: 99%
“…Considerations related to weight of evidence for MOA have been additionally articulated in a subsequent publication (Meek et al 2014b) and evolved in international collaborative efforts on adverse outcome pathways (AOPs) (OECD Handbook 2016;Becker et al 2015;Edwards et al 2016). The US EPA (2014) guidance on Data-Derived Extrapolation Factors also contributes significantly to CSAF evolution by encouraging the identification and use of TK or TD data to inform the magnitude of interspecies differences and human variability (e.g.…”
Section: Updating and Revision Of The Guidancementioning
confidence: 99%
“…DNA damage) are expected to appear at doses below or similar to those associated with later key events (e.g. tumour formation) (61). In mice, no mutagenic response was detected up to tested concentrations of acrylamide almost an order of magnitude higher than the BMDs for tumour induction.…”
Section: Discussionmentioning
confidence: 99%
“…To derive a MOA based on the International Programme on Chemical Safety (IPCS)/ (ILSI) MOA framework (Meek et al 2014; Boobis et al, 2006; Meek et al, 2003; Sonich-Mullin et al, 2001), key events were identified by interrogating all genomics data based on functional annotation. Key events are empirically observable, necessary precursor events in the MOA or biologically based markers for such events (US EPA, 2005).…”
Section: Genomics Approaches (Ra2 and Ra3)mentioning
confidence: 99%